Analysis of Factors Related to the Risk of Hypertension Events at Royal Prima Medan Hospital in 2021 - Li Wei; Florenly Florenly; Liena Liena; Fioni Fioni (Budapest International Research and Critics University, 2021)
Hypertension is estimated to be the cause of death of 7.1 million people worldwide or about 13% of the total death. The purpose of the study is to find out the analysis of factors related to the risk of hypertension events. This type of quantitative research is a non-experimental descriptive approach. The study was conducted at Royal Prima Hospital, April-June 2021. The study population of all inpatients/street, Structural Equation Modelling (SEM) sampling technique sample numbered 200 people. Instrument research tension meter, stethoscope, digital scales, meter, and questionnaire. Bivariate (Chi-square) and multivariate (multiple logistic regression) analysis, 0.05 degree of confidence. The results of statistical tests using Chi-Square, the majority of respondents aged 56-65 years 124 people (62%), p-value 0,000, the majority of female respondents are 141 people (72%), p-value 0,000, the majority of respondents have a history of hypertension in the family of 161 people (81%), p-value 0,006, the majority of respondents do not smoke 146 people (73%), p-value 0,044, the majority of respondents dietary patterns rarely consume fat by 156 people (78%), p-value 0.026, the majority of respondents did not consume alcohol 171 people (86%), p- value 0.016, these variables had a meaningful relationship with p-value < 0.05. While the majority of obese respondents amounted to 138 people with a percentage (69%), had no association with p-value 0.117 (>0.05). In the results of multivariate analysis, the most dominant factor determining the incidence of hypertension is the sex variable, p-value (0.000) < 0.05, or value 21,200, meaning that the sex has a 21,200 chance of developing hypertension. Conclusions of research variables age, gender, family history, smoking, diet, alcohol consumption have an association with the incidence of hypertension, the most dominant factor is gender. It is expected that all communities can still maintain a healthy lifestyle, to avoid various diseases, especially non-communicable diseases.